HISTOPATHOLOGICAL PICTURE OF WHITE RATS HEART POST APPLICATION OF MIMOSIN FROM SIMPLISIA LAMTORO LEAF - Ni Made Ayu Suastami; I Ketut Berata; Ni Luh Eka Setiasih; Samsuri; Luh Made Sudimartini; I Ketut Suatha (Buletin Veteriner Udayana, 2024)
Mimosine is a toxic compound that can be found in the leaves of the lamtoro plant (Leucaena leucocephala). Toxicity that occurs in livestock depends on the concentration of mimosine in the feed and the length of time it is administered. This study aims to determine the histopathological picture of the heart of white rats (Rattus norvegicus) given mimosine from lamtoro leaf simplicia at different doses. The research used 2 months old Wistar male white rats weighing 300-350 grams. The 20 experimental animals used were divided into 4 treatment groups, namely P0 (negative control) without mimosine, P1 (positive control) given standard mimosine 5 mg/head/day, P2 given lamtoro leaf simplicia at a dose of 50 mg/head/day, and P3 simplicia lamtoro leaves at a dose of 150 mg/head/day. Mimosine was given orally for 14 days using a probe. On the 15th day, a necropsy was performed, the heart organ was removed and placed in 10% NBF. Next, it is processed to make histopathological preparations with HE staining. Histopathological examination was carried out including three variables: congestion, bleeding and necrosis. The severity of the lesion was scored, namely 0, 1, 2, and 3 respectively for normal, mild, moderate, and severe lesions. The data was then analyzed using the non-parametric Kruskal-Wallis and Mann-Whitney tests. The results of the study showed that administration of mimosine from lamtoro leaf simplicia could cause histopathology in the form of congestion, bleeding and necrosis lesions compared to controls and there was no effect on the difference in the dose of mimosine from lamtoro leaf simplicia between doses of 50 mg/head/day and 150 mg/head/day.